A method for preparing whole-biological enzyme-degradable particles

By blending starch, epoxy soybean oil, modified rigid particle composite cellulose with polylactic acid, and processing through hot pressing process, a full bioenzyme degradation membrane with high mechanical properties and rapid degradation is solved, and the problem of poor mechanical properties of existing bio-based polymers is achieved, and cost reduction and performance improvement are achieved.

CN119192807BActive Publication Date: 2025-03-18FUJIAN DELV NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411724414.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-18
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Due to the lack of mechanical properties of existing bio-based polymers, they limit their application in biomedicine, textiles, agriculture and other fields, and are expensive and difficult to promote and popularize.

Method used

The preparation method of whole-biozyme degraded particles is adopted to prepare a full-biozyme degraded membrane with high mechanical properties by blending starch, epoxy soybean oil, modified rigid particle composite cellulose with polylactic acid and processing it through hot pressing.

Benefits of technology

The high mechanical properties and rapid degradation of all bioenzyme-degraded particles and their products are achieved, reducing production costs, and improving the compatibility and decomposition efficiency of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of a fully bio-enzyme-degradable particle, and relates to the technical field of biodegradable materials. The invention uses 5,6-epoxyhexyltriethoxysilane to modify modified calcium carbonate and a trace amount of ferrosoferric oxide, and then disperses them in a cellulose hydrogel precursor solution. When cellulose self-associates into a three-dimensional network structure, the particles are firmly fixed in its micro-nano pore structure, thereby enhancing the stability of the degradation particle matrix, using starch as a water absorbent, epoxy soybean oil as a plasticizer, and modified rigid particle composite cellulose as a reinforcement, and blending with polylactic acid as a carrier, and then, by hot pressing and curing to obtain degradation particles, the inorganic nanoparticles are more firmly combined with the matrix under the dual influence of temperature and pressure, thereby enhancing the mechanical properties of the film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biodegradable materials, in particular to a method for preparing fully biological enzyme-degradable particles. Background Art

[0002] Bio-based polymers are an environmentally friendly material made from renewable resources. As a substitute for traditional non-renewable petroleum-based polymers, they are gaining more and more attention as the environment deteriorates and petroleum resources become increasingly scarce. However, the existing bio-based polymers are limited in their application due to their unsatisfactory mechanical properties. Polylactic acid is an important biodegradable polymer with good mechanical processing properties. Its rigidity is the highest among common biodegradable polymers; therefore, it is widely used in biomedicine, textiles, agriculture and other fields. However, polylactic acid is expensive and difficult to popularize. It is usually blended with lower-cost substances such as starch to prepare biodegradable plastics to reduce its cost. The melting temperature of native starch is higher than its decomposition temperature, so it cannot be heat-processed. Generally, starch is heat-plasticized, but its plastic is hydrophilic, while the degradable resin is lipophilic. When the two are blended, the interfacial bonding force of the blend is weak, which affects the mechanical properties of the product. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing whole-biological enzyme-degradable particles to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing whole-biological enzyme-degradable particles, comprising the following preparation steps:

[0005] (1) Mix the rigid particles and 95% ethanol aqueous solution, ultrasonicate at 21kHz for 18-30min, adjust the solution pH to 7-8 with aqueous ammonia, add 5,6-epoxyhexyltriethoxysilane, heat to 45-55°C under nitrogen atmosphere, react for 1-3h, add oleic acid, stir at 300-700rpm for 10-30min, continue to react for 1-3h, cool to room temperature, and wash with cyclohexane for 3-8 times to obtain modified rigid ions;

[0006] (2) Sodium hydroxide, urea and deionized water are mixed, stirred at 100 rpm for 30-50 min, bacterial cellulose is added, and the mixture is allowed to stand at -10--15°C for 100-200 min, then stirred at 400-700 rpm for 20-50 min, modified rigid particles are added, and the mixture is dispersed by ultrasonication and degassed by centrifugation to obtain modified rigid particle composite cellulose;

[0007] (3) Corn starch and epoxidized soybean oil are mixed, stirred at 700-1000 rpm for 10-30 min, modified rigid particle composite cellulose and polylactic acid are added, and extrusion granulation is performed to obtain fully bio-enzyme-degradable particles.

[0008] Furthermore, the rigid particles in step (1) are composed of nano calcium carbonate and nano ferrosoferric oxide in a mass ratio of 10:0.1~1.

[0009] Furthermore, in step (1), the mass ratio of the rigid particles, 95% ethanol aqueous solution, 5,6-epoxyhexyltriethoxysilane, and oleic acid is 2:100:1~3:1~5.

[0010] Furthermore, the frequency of the ultrasonic dispersion in step (2) is 21 kHz and the time is 10 to 30 minutes.

[0011] Furthermore, the rotation speed of the centrifugal degassing in step (2) is 4500-8000 rpm and the time is 30-70 min.

[0012] Furthermore, in step (2), the mass ratio of sodium hydroxide, urea, deionized water, bacterial cellulose, and modified rigid particles is 7:12:90:2~5:0.5~2.

[0013] Furthermore, the molecular weight of the polylactic acid in step (3) is 8×10 4 .

[0014] Furthermore, the temperature of the extrusion granulation in step (3) is 170-230°C.

[0015] Furthermore, in step (3), the mass ratio of the corn starch, epoxy soybean oil, modified rigid particle composite cellulose, and polylactic acid is 1:3~6:4~8:12~20.

[0016] Furthermore, any method for preparing fully bio-enzyme-degradable particles is characterized in that the fully bio-enzyme-degradable particles are treated by a hot pressing process, at 150°C, first at a pressure of 6 MPa for 20 minutes, and then at a pressure of 60~100 MPa for 5 minutes, to obtain a fully bio-enzyme-degradable film with a thickness of 0.01~0.1 mm.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0018] The degradable particles of the present invention use starch as a water absorbent, epoxidized soybean oil as a plasticizer, and modified rigid particle composite cellulose as a reinforcement, which are blended with polylactic acid as a carrier, wherein the organic carbon chain on the surface of calcium carbonate can be entangled with the molecular chain of polylactic acid, thereby improving the compatibility between different substances, and serving as a physical crosslinking point to increase the intermolecular force of the blending system, so that the expansion of cracks in the degradable particles and their products is subject to a certain resistance, and at the same time, the active surface and active atomic center of the modified rigid particles interact with the polymer molecular chain to form a "filamentous connection" structure, which can better transmit the strain between the matrixes inside the degradable particles, thereby achieving strong mechanical properties, and the addition of nano rigid particles can promote the Crystallization, while causing changes in the structure of the polymer system. With the assistance of the water absorbent, the ester bonds in the polylactic acid molecules will first undergo hydrolysis, gradually shedding inorganic ions, allowing the degradable particles and the degradable products to have a more sufficient contact area, thereby accelerating the decomposition. Then, the film is obtained by hot pressing and curing. Under the dual influence of temperature and pressure, the cellulose drives the matrix aggregation state to change, while making the inorganic nanoparticles and the polymer system more firmly combined. In addition, the epoxy groups in the epoxy soybean oil and 5,6-epoxyhexyltriethoxysilane enable the matrix between the polymers to hybridize, and can enhance the curing by reacting with the blend containing amino or carboxyl groups, thereby enhancing the mechanical properties of the degradable particles and their products.

[0019] The modified rigid particles in the present invention utilize silanol generated by hydrolysis of 5,6-epoxyhexyltriethoxysilane to react with hydroxyl groups on the surface of nano rigid particles, i.e., modify modified calcium carbonate and a trace amount of ferroferric oxide. Then, oleic acid is used as an aid to form a steric hindrance on the surface of the rigid particles through its long chain structure, offset the gravitational force between some particles, increase the distance between particles, and fully disperse the nano particles, thereby reducing the amount of ferroferric oxide used. The iron element with a suitable concentration promotes the growth of biodegradable enzymes, and can chelate with organic acids produced by fungi in the soil themselves or indirectly generated, which is conducive to the participation of hydronium ions and hydroxyl radicals in the degradation reaction of the degradation particles, thereby accelerating the degradation efficiency of the degradation particles. The particles are then dispersed in a cellulose hydrogel precursor solution, and when cellulose self-associates into a three-dimensional network structure, the particles are attached thereto. When the degradation particle matrix solidifies, the hydroxyl groups on the particle surface interact with the hydroxyl groups in the cellulose and are firmly fixed in the micro-nano pore structure in the cellulose hydrogel under the action of hydrogen bonds, thereby enhancing the stability of the matrix. The metal nano particles can accelerate the thermal degradation of cellulose, further improving the degradation rate of the degradation particles. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0021] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of the whole biological enzyme degradable particles and the corresponding prepared films in the following examples are as follows:

[0022] Mechanical properties: The yield stress and Elmendorf tear strength of the examples and comparative examples of the same size were tested according to JIS K7127 and ISO 6383-2, respectively.

[0023] Biodegradability: The same size of the examples and comparative examples were taken according to ISO 16929 to test the biodegradability of the samples on the 50th day.

[0024] Example 1; (1) Mix nano calcium carbonate and nano ferroferric oxide in a mass ratio of 10:0.1 to obtain rigid particles; mix the rigid particles and 95% ethanol aqueous solution, ultrasonicate at 21kHz for 18 minutes, adjust the solution pH to 7 with ammonia water, add 5,6-epoxyhexyltriethoxysilane, heat to 45°C under nitrogen atmosphere, react for 1 hour, add oleic acid, stir at 300rpm for 10 minutes, continue to react for 1 hour, cool to room temperature, and wash with cyclohexane 3 times to obtain modified rigid ions; the mass ratio of the rigid particles, 95% ethanol aqueous solution, 5,6-epoxyhexyltriethoxysilane and oleic acid is 2:100:1:1;

[0025] (2) Sodium hydroxide, urea and deionized water were mixed, stirred at 100 rpm for 30 min, bacterial cellulose was added, and the mixture was allowed to stand at -10°C for 100 min, then stirred at 400 rpm for 20 min, modified rigid particles were added, and ultrasonic dispersion was performed at a frequency of 21 kHz for 10 min, and centrifugal degassing was performed at a speed of 4500 rpm for 30 min to obtain modified rigid particle composite cellulose; the mass ratio of sodium hydroxide, urea, deionized water, bacterial cellulose and modified rigid particles was 7:12:90:2:0.5;

[0026] (3) Corn starch and epoxidized soybean oil were mixed and stirred at 700 rpm for 10 min. Modified rigid particle composite cellulose with a molecular weight of 8×10 4The polylactic acid was extruded and granulated at 170°C to obtain fully bio-enzyme-degradable particles; the fully bio-enzyme-degradable particles were subjected to a hot pressing process, at 150°C, firstly at a pressure of 6MPa for 20min, and then at a pressure of 60MPa for 5min, to obtain a fully bio-enzyme-degradable film with a thickness of 0.01mm; the corn starch, epoxidized soybean oil, modified rigid particle composite cellulose, molecular weight 8×10 4 The mass ratio of polylactic acid is 1:3:4:12.

[0027] Example 2; (1) Nano calcium carbonate and nano ferroferric oxide were mixed in a mass ratio of 10:0.6 to obtain rigid particles; the rigid particles were mixed with a 95% ethanol aqueous solution, ultrasonicated at 21kHz for 24 minutes, the pH of the solution was adjusted to 7.5 with aqueous ammonia, 5,6-epoxyhexyltriethoxysilane was added, the temperature was raised to 50°C under a nitrogen atmosphere, the reaction was continued for 2 hours, oleic acid was added, stirred at 500rpm for 20 minutes, the reaction was continued for 2 hours, cooled to room temperature, and washed with cyclohexane 5 times to obtain modified rigid ions; the mass ratio of the rigid particles, 95% ethanol aqueous solution, 5,6-epoxyhexyltriethoxysilane and oleic acid was 2:100:2:3;

[0028] (2) Sodium hydroxide, urea and deionized water were mixed, stirred at 100 rpm for 40 min, bacterial cellulose was added, and the mixture was allowed to stand at -13°C for 150 min, then stirred at 550 rpm for 35 min, modified rigid particles were added, and ultrasonic dispersion was performed at a frequency of 21 kHz for 20 min, and centrifugal degassing was performed at a speed of 6200 rpm for 50 min to obtain modified rigid particle composite cellulose; the mass ratio of sodium hydroxide, urea, deionized water, bacterial cellulose and modified rigid particles was 7:12:90:3.5:1.2;

[0029] (3) Corn starch and epoxidized soybean oil were mixed and stirred at 850 rpm for 20 min. Modified rigid particle composite cellulose with a molecular weight of 8×10 4 The polylactic acid is extruded and granulated at 200°C to obtain fully bio-enzyme-degradable particles; the fully bio-enzyme-degradable particles are subjected to a hot pressing process, at 150°C, firstly at a pressure of 6MPa for 20min, and then at a pressure of 90MPa for 5min, to obtain a fully bio-enzyme-degradable film with a thickness of 0.05mm; the corn starch, epoxy soybean oil, modified rigid particle composite cellulose, molecular weight 8×10 4 The mass ratio of polylactic acid is 1:4.5:6:16.

[0030] Example 3; (1) Mix nano calcium carbonate and nano ferroferric oxide in a mass ratio of 10:1 to obtain rigid particles; mix the rigid particles and 95% ethanol aqueous solution, ultrasonicate at 21kHz for 30 minutes, adjust the solution pH to 8 with ammonia water, add 5,6-epoxyhexyltriethoxysilane, heat to 55°C under nitrogen atmosphere, react for 3 hours, add oleic acid, stir at 700rpm for 30 minutes, continue to react for 3 hours, cool to room temperature, and wash with cyclohexane 8 times to obtain modified rigid ions; the mass ratio of the rigid particles, 95% ethanol aqueous solution, 5,6-epoxyhexyltriethoxysilane and oleic acid is 2:100:3:5;

[0031] (2) Sodium hydroxide, urea and deionized water were mixed, stirred at 100 rpm for 50 min, bacterial cellulose was added, and the mixture was allowed to stand at -15°C for 200 min, then stirred at 700 rpm for 50 min, modified rigid particles were added, and ultrasonic dispersion was performed at a frequency of 21 kHz for 30 min, and centrifugal degassing was performed at a speed of 8000 rpm for 70 min to obtain modified rigid particle composite cellulose; the mass ratio of sodium hydroxide, urea, deionized water, bacterial cellulose and modified rigid particles was 7:12:90:5:2;

[0032] (3) Corn starch and epoxidized soybean oil were mixed and stirred at 1000 rpm for 30 min. Modified rigid particle composite cellulose with a molecular weight of 8×10 4 The polylactic acid was extruded and granulated at 230°C to obtain fully bio-enzyme-degradable particles; the fully bio-enzyme-degradable particles were subjected to a hot pressing process, at 150°C, firstly at a pressure of 6MPa for 20min, and then at a pressure of 100MPa for 5min, to obtain a fully bio-enzyme-degradable film with a thickness of 0.1mm; the corn starch, epoxidized soybean oil, modified rigid particle composite cellulose, molecular weight 8×10 4 The mass ratio of polylactic acid is 1:6:8:20.

[0033] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: nano calcium carbonate and nano ferrosoferric oxide are mixed in a mass ratio of 10:0.6 to obtain rigid particles; the rigid particles and 95% ethanol aqueous solution are mixed, ultrasonicated at 21kHz for 24min, the pH value of the solution is adjusted to 7.5 with ammonia water, 5,6-epoxyhexyltriethoxysilane is added, and the temperature is raised to 50°C under a nitrogen atmosphere, reacted for 2h, cooled to room temperature, and washed with cyclohexane 5 times to obtain modified rigid ions; the mass ratio of the rigid particles, 95% ethanol aqueous solution and 5,6-epoxyhexyltriethoxysilane is 2:100:2; the remaining steps are the same as those in Example 2.

[0034] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (1) is omitted; the remaining steps are the same as those of Example 2.

[0035] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (1) is different. Step (1) is changed to: mix nano calcium carbonate and 95% ethanol aqueous solution, ultrasonicate at 21kHz for 24 minutes, adjust the pH of the solution to 7.5 with ammonia water, add 5,6-epoxyhexyltriethoxysilane, heat to 50°C under nitrogen atmosphere, react for 2 hours, add oleic acid, stir at 500rpm for 20 minutes, continue to react for 2 hours, cool to room temperature, wash with cyclohexane 5 times, and obtain modified calcium carbonate; the mass ratio of the nano calcium carbonate, 95% ethanol aqueous solution, 5,6-epoxyhexyltriethoxysilane and oleic acid is 2:100:2:3; the remaining steps are the same as Example 2.

[0036] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (1) is different. Step (1) is changed to: mix nano-iron tetroxide and 95% ethanol aqueous solution, ultrasonicate at 21kHz for 24min, adjust the pH value of the solution to 7.5 with aqueous ammonia, add 5,6-epoxyhexyltriethoxysilane, heat to 50°C under nitrogen atmosphere, react for 2h, add oleic acid, stir at 500rpm for 20min, continue to react for 2h, cool to room temperature, wash with cyclohexane 5 times, and obtain modified iron tetroxide; the mass ratio of the nano-iron tetroxide, 95% ethanol aqueous solution, 5,6-epoxyhexyltriethoxysilane and oleic acid is 2:100:2:3; the remaining steps are the same as those in Example 2.

[0037] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that there is no step (1), and step (2) is changed to: sodium hydroxide, urea and deionized water are mixed, stirred at 100 rpm for 40 min, bacterial cellulose is added, and the mixture is allowed to stand at -13°C for 150 min, then stirred at 550 rpm for 35 min, and centrifuged for degassing at a speed of 6200 rpm for 50 min to obtain cellulose; the mass ratio of sodium hydroxide, urea, deionized water and bacterial cellulose is 7:12:90:3.5; the remaining steps are the same as those in Example 2.

[0038] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that there is no step (2), and step (3) is changed to: corn starch and epoxidized soybean oil are mixed, stirred at 850 rpm for 20 min, and modified rigid particles with a molecular weight of 8×10 4The polylactic acid is extruded and granulated at 200°C to obtain fully bio-enzyme-degradable particles; the fully bio-enzyme-degradable particles are subjected to a hot pressing process at 150°C, first at a pressure of 6MPa for 20min, and then at a pressure of 90MPa for 5min to obtain a fully bio-enzyme-degradable film with a thickness of 0.05mm; the corn starch, epoxidized soybean oil, modified rigid particles, and a molecular weight of 8×10 4 The mass ratio of the polylactic acid is 1:4.5:6:16; the remaining steps are the same as in Example 2.

[0039] Comparative Example 7: The difference between Comparative Example 7 and Example 2 is that step (3) is different, and step (3) is changed to: epoxy soybean oil, modified rigid particle composite cellulose, molecular weight 8×10 4 The polylactic acid is mixed and extruded at 200°C to obtain fully bio-enzyme-degradable particles; the fully bio-enzyme-degradable particles are subjected to a hot pressing process, at 150°C, firstly at a pressure of 6MPa for 20min, and then at a pressure of 90MPa for 5min, to obtain a fully bio-enzyme-degradable film with a thickness of 0.05mm; the epoxy soybean oil, the modified rigid particle composite cellulose, and the molecular weight of 8×10 4 The mass ratio of the polylactic acid is 4.5:6:16; the remaining steps are the same as in Example 2.

[0040] Comparative Example 8: The difference between Comparative Example 8 and Example 2 is that step (3) is different. Step (3) is changed to: corn starch and epoxidized soybean oil are mixed, stirred at 850 rpm for 20 min, and modified rigid particle composite cellulose with a molecular weight of 8×10 4 The polylactic acid is extruded and granulated at 200°C to obtain fully bio-enzyme-degradable particles; the fully bio-enzyme-degradable particles are heated to 250°C, then smeared on a template, and cured at 50°C for 2h to obtain a fully bio-enzyme-degradable film with a thickness of 0.05 mm; the corn starch, epoxidized soybean oil, modified rigid particle composite cellulose, and molecular weight 8×10 4 The mass ratio of the polylactic acid is 1:4.5:6:16; the remaining steps are the same as in Example 2.

[0041] Effect example

[0042] Table 1 below shows the performance analysis results of the full-biological enzyme-degradable particles of Examples 1 to 3 of the present invention and Comparative Examples 1 to 8.

[0043] Table 1

[0044]

[0045] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention uses 5,6-epoxyhexyltriethoxysilane to generate silanol groups through hydrolysis to react with hydroxyl groups on the surface of nano rigid particles, that is, to modify modified calcium carbonate and a trace amount of ferrosoferric oxide. Then, oleic acid is used as an auxiliary to form a steric hindrance on the surface of the rigid particles through its long chain structure, increase the distance between the particles, and fully disperse the nano particles, thereby reducing the amount of ferrosoferric oxide. The iron element with a suitable concentration promotes the growth of biodegradable enzymes and accelerates the degradation efficiency of the degradation particles. Then, it is dispersed in the cellulose hydrogel precursor solution. When the cellulose self-associates into a three-dimensional network structure, the particles are attached to it. When the degradation particle matrix solidifies, the hydroxyl groups on the particle surface interact with the hydroxyl groups in the cellulose and are firmly fixed in the micro-nano pore structure in the cellulose hydrogel under the action of hydrogen bonds, thereby enhancing the stability of the degradation particle matrix. The metal nanoparticles can accelerate the thermal degradation of cellulose and further improve the degradation rate of the degradation particle matrix. Starch is used as a water absorbent, epoxy soybean oil is used as a plasticizer, and the modified rigid particles are composited with cellulose as a reinforcement. Blended with polylactic acid as a carrier, the organic carbon chain on the surface of calcium carbonate can be entangled with the molecular chain of polylactic acid, improving the compatibility between different substances. At the same time, the active surface and active atomic center of the nanoparticles interact with the polymer molecular chain to form a "filamentous connection" structure, which can better transmit the strain between the matrix, thereby achieving stronger mechanical properties. The addition of nano rigid particles can promote the crystallization of polylactic acid and change the structure of the polymer system. Under the auxiliary action of the water absorbent, the ester bond in the polylactic acid molecule will first be hydrolyzed, and then gradually The inorganic ions are gradually shed, so that the matrix and the degradation products have a more sufficient contact area, thereby accelerating the decomposition. Then, the film is obtained by hot pressing and curing. Under the dual influence of temperature and pressure, the cellulose drives the matrix aggregation state to change, and at the same time, the inorganic nanoparticles and the degradation particle matrix are more firmly combined. In addition, the epoxy groups in epoxy soybean oil and 5,6-epoxyhexyltriethoxysilane enable the matrix between the polymers to hybridize, and the curing can be enhanced by reacting with the blend containing amino or carboxyl groups, thereby enhancing the mechanical properties of the degradation particles and their products.

[0046] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing whole-biological enzyme-degradable particles, characterized in that: The method comprises the following preparation steps: (1) Mixing nano calcium carbonate and nano ferroferric oxide in a mass ratio of 10:0.1-1 to obtain rigid particles; mixing the rigid particles and a 95% ethanol aqueous solution, ultrasonicating at 21kHz for 18-30min, adjusting the pH value of the solution to 7-8 with aqueous ammonia, adding 5,6-epoxyhexyltriethoxysilane, heating to 45-55°C under a nitrogen atmosphere, reacting for 1-3h, adding oleic acid, stirring at 300-700rpm for 10-30min, continuing the reaction for 1-3h, cooling to room temperature, washing with cyclohexane for 3-8 times, and obtaining modified rigid particles; the mass ratio of the rigid particles, 95% ethanol aqueous solution, 5,6-epoxyhexyltriethoxysilane, and oleic acid is 2:100:1-3:1-5; (2) Sodium hydroxide, urea and deionized water are mixed, stirred at 100 rpm for 30-50 min, bacterial cellulose is added, and the mixture is allowed to stand at -10--15°C for 100-200 min, then stirred at 400-700 rpm for 20-50 min, modified rigid particles are added, and the mixture is dispersed by ultrasonication and degassed by centrifugation to obtain modified rigid particle composite cellulose; (3) Corn starch and epoxidized soybean oil are mixed, stirred at 700-1000 rpm for 10-30 min, modified rigid particle composite cellulose and polylactic acid are added, and extrusion granulation is performed to obtain fully bio-enzyme-degradable particles.

2. The method for preparing a fully biodegradable enzyme-degradable particle according to claim 1, characterized in that: The frequency of the ultrasonic dispersion in step (2) is 21 kHz and the time is 10 to 30 minutes.

3. The method for preparing a whole-organic enzyme-degradable granule according to claim 1, characterized in that: The rotation speed of the centrifugal degassing in step (2) is 4500-8000 rpm and the time is 30-70 min.

4. The method for preparing a whole-organic enzyme-degradable granule according to claim 1, characterized in that: The mass ratio of sodium hydroxide, urea, deionized water, bacterial cellulose and modified rigid particles in step (2) is 7:12:90:2~5:0.5~2.

5. The method for preparing a whole-organic enzyme-degradable granule according to claim 1, characterized in that: The molecular weight of the polylactic acid in step (3) is 8×10 4 .

6. The method for preparing a whole-organic enzyme-degradable granule according to claim 1, characterized in that: The temperature of the extrusion granulation in step (3) is 170-230°C.

7. The method for preparing a whole-organic enzyme-degradable granule according to claim 1, characterized in that: In step (3), the mass ratio of corn starch, epoxy soybean oil, modified rigid particle composite cellulose and polylactic acid is 1:3~6:4~8:12~20.

8. The method for preparing the whole-organic enzyme-degradable particles according to any one of claims 1 to 7, characterized in that: The fully bio-enzyme-degradable particles are processed by hot pressing, at 150° C., firstly at a pressure of 6 MPa for 20 minutes, and then at a pressure of 60-100 MPa for 5 minutes, to obtain a fully bio-enzyme-degradable film with a thickness of 0.01-0.1 mm.

Citation Information

Patent Citations

  • Shock-absorbing sole and shock-absorbing shoe

    CN111150173A

  • Modified full-bio-based PBAT biodegradable plastic and preparation method thereof

    CN113549307A